In situ Forming Hyperbranched PEG—Thiolated Hyaluronic Acid Hydrogels With Honey-Mimetic Antibacterial Properties - Vasquez, Jeddah Marie; Idrees, Ayesha; Carmagnola, Irene; Sigen, Aa; McMahon, Sean; Marlinghaus, Lennart; Ciardelli, Gianluca; Greiser, Udo; Tai, Hongyun; Wang, Wenxin; Salber, Jochen; Chiono, Valeria (Frontiers in Bioengineering and Biotechnology, 2021)
The increasing resistance of bacteria to approved antibiotics makes surgery and treatment of bacterial infections increasingly difficult. In recent years, complementary strategies to classical antibiotic therapy have therefore gained in importance. One of these strategies is the use of medicinal honey in the treatment of wounds. One of the bactericidal effects of honey is based on the in situ generation of hydrogen peroxide through the activity of glucose oxidase (GO). The strategy here is to mimic this antibacterial redox effect of honey in an injectable, biocompatible, and rapidly forming hydrogel. This was obtained by thiol-ene click reaction between hyperbranched polyethylene glycol diacrylate (HB PEGDA), synthesized using Reversible Addition-Fragmentation chain-Transfer (RAFT) polymerization, and thiolated hyaluronic acid (HA-SH). After mixing 500 µL HB PEGDA (10%, w/w) and 500 µL HA-SH (1%, w/w) solutions, hydrogel formed in ~60 s, as assessed by tube inverting test. HB PEGDA/HA-SH 10.0-1.0 hydrogel (200 µL) was resistant to in vitro dissolution in water for at least 64 days, absorbing up to 130 wt.% water. Varying GO amounts (0-500 U/L) and constant glucose content (2.5 wt.%) were loaded in HB PEGDA and HA-SH solutions respectively, before hydrogel formation. Then, the release of H2O2 was evaluated through a pertitanic acid assay. GO content of 250 U/L was selected, allowing the formation of 10.8±1.4 mmol H2O2/L hydrogel in 24 h. The cytocompatibility of HB PEGDA/HA-SH 10.0-1.0 hydrogels loaded with different GO activities (≤ 500 U/L) at constant glucose amount (2.5 wt.%) was investigated by in vitro assays at 24 h with L929 and HaCaT cells, according to DIN EN ISO 10993-5. They showed cytocompatibility for GO activity up to 250 U/L for both cell lines. The antibacterial activity of HB PEGDA/HA-SH 10-1.0 hydrogels loaded with increasing amounts of GO was demonstrated against various gram-positive and gram-negative strains using agar diffusion tests. For all gram-positive bacterial strains, increasing efficacy was measured with increasing GO activity. For Pseudomonas strains, efficacy was shown only from an activity of 125 U/L and for E. coli and A. baumanii only from 250 U/L. These honey-mimetic hydrogels are promising formulations for future treatments in wound care.